2023
DOI: 10.1093/ehjdh/ztad004
|View full text |Cite
|
Sign up to set email alerts
|

A clinician-to-clinician universal electronic consultation programme at the cardiology department of a Galician healthcare area improves healthcare accessibility and outcomes in elderly patients

Abstract: Aim We aimed to assess the longer-term results (accessibility, and hospital admissions and mortality) in elderly patients referred to a cardiology department (CD) from primary care using an e-consultation in outpatient care. Methods We included 9,963 patients >80 years from January 1, 2010, to December 31, 2019. Until 2012, all patients were attended in an in-person consultation (2010-2012). In 2013, we instituted an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Our study has demonstrated that this programme is associated with a reduction in waiting lists and better health outcomes, for all patients 4,14 including those with a previous diagnosis of cardiac disease such as HF 23 and AF 24 . In addition, this programme has significantly improved the accessibility of the CD for patients who live far from the hospital, particularly those over 80 years old 25 . Our study has also highlighted that clinician‐to‐clinician programmes, such as e‐consultation, can enhance healthcare equity and quality, which is especially important for vulnerable patients, including women.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Our study has demonstrated that this programme is associated with a reduction in waiting lists and better health outcomes, for all patients 4,14 including those with a previous diagnosis of cardiac disease such as HF 23 and AF 24 . In addition, this programme has significantly improved the accessibility of the CD for patients who live far from the hospital, particularly those over 80 years old 25 . Our study has also highlighted that clinician‐to‐clinician programmes, such as e‐consultation, can enhance healthcare equity and quality, which is especially important for vulnerable patients, including women.…”
Section: Discussionmentioning
confidence: 68%
“…24 In addition, this programme has significantly improved the accessibility of the CD for patients who live far from the hospital, particularly those over 80 years old. 25 Our study has also highlighted that clinician-to-clinician programmes, such as e-consultation, can enhance healthcare equity and quality, which is especially important for vulnerable patients, including women. We have previously reported inequalities in the care of women and believe that our findings address this issue.…”
Section: Allmentioning
confidence: 79%
“…They can also significantly reduce the need for face-to-face consultations, with reductions ranging from 8.9% to 51%, depending on the clinical setting and specialty. 28 Our group has previously reported the benefits of implementing an e-consultation program as the first step for all PCP referrals to our CD. This initiative improved 1-year outcomes compared to a previous period of in-person consultation for all referrals.…”
Section: Discussionmentioning
confidence: 99%
“…The development of integrated health records can make clinician-to-clinician communication more fluent and contain all the necessary information to optimize the resolution of the HF patient clinical problem, 21 and also our publications about our experience. 23–25 …”
Section: Discussionmentioning
confidence: 99%